The Military and Democracy in Indonesia Challenges, Politics, and Power - Rabasa, Angel (RAND Corporation, 2002)
The military is one of the few institutions that cut across the divides of Indonesian society. As it continues to play a critical part in determining Indonesia's future, the military itself is undergoing profound change. The authors of this book examine the role of the military in politics and society since the fall of President Suharto in 1998. They present several strategic scenarios for Indonesia, which have important implications for U.S.-Indonesian relations, and propose goals for Indonesian military reform and elements of a U.S. engagement policy.